Hypertensive disorders first identified in pregnancy increase risk for incident prehypertension and hypertension in the year after delivery. Issue 4 (April 2016) - Black, Mary Helen; Zhou, Hui; Sacks, David A.; Dublin, Sascha; Lawrence, Jean M.; Harrison, Teresa N.; Reynolds, Kristi
Abstract : Background: Hypertensive disorders in pregnancy, including preeclampsia/eclampsia (PE/E) are associated with long-term cardiovascular disease risk. However, little is known about the effect of these conditions on risk for prehypertension (preHTN) or hypertension (HTN) in the early years after delivery. Methods: The cohort consisted of women who had prenatal care and delivered a live singleton neonate at Kaiser Permanente Bellflower Medical Center in 2005–2010. Women with prepregnancy HTN or preHTN were excluded from analysis. Multivariable robust Poisson regression models were used to assess associations between any hypertensive disorder or PE/E and development of preHTN/HTN in the year after delivery, adjusted for maternal age, race/ethnicity, parity, smoking, prepregnancy weight status, gestational weight gain, gestational diabetes, and gestational age. Results: Among 5960 women who were normotensive prior to pregnancy, 358 (6.0%) developed a hypertensive disorder in pregnancy, of whom 215 (60.1%) had PE/E. Overall, 63 (1.1%) developed HTN and 902 (15.1%) preHTN in the year after delivery. After accounting for all potential confounders, women with a hypertensive disorder in pregnancy and those with PE/E were 2.36 (95% confidence interval: 1.97–2.83) and 2.48 (95% confidence interval: 1.99–3.11) times as likely, respectively, to develop preHTN/HTN in the year after delivery as those without pregnancy-related HTN. Results were similar with and without adjustment for gestational diabetes. Conclusion: Our findings highlight the need for prospective studies aimed at determining whether early postpartum screening and improved follow-up of women with hypertensive disorders first identified in pregnancy may prevent future cardiovascular disease. Abstract : Supplemental Digital Content is available in the text